Clinical Profiling and Comparative Assessment of Selective Serotonin Reuptake Inhibitors and Tricyclic Antidepressants in the Management of Postpartum Depression - Cholamugath, Shinu; Chanaparambil, Mukhthar Ali; Paul, Minu; Moosa, Mujeeba (Indian Journal of Pharmacy Practice)
Objectives: To compare and assess the effectiveness of SSRIs and TCAs and to interpret the patient clinical data on PPD and to state the relation of clinical data such as patient demographics, pregnancy complication, patient history, socio-economic status, history with PPD. Materials and Methods: An observational cohort study with 6-months duration was conducted among 30 women in the age group 18-45 years, in a tertiary care hospital at Perintalmanna, Malappuram, Kerala. Results: About 66.7% (n=20) of patients treated with SSRI and about 33.3% (n=10) with TCA. The statistical data shows that SSRI is efficient compared to TCA for the treatment of PPD with symptom reduction and improvement in functioning with a p<0.001. Paired t-test shows initial EPDS score have a mean of 18.8667±2.44573 and final EPDS score had a mean of 14.0667±2.247 and initial MADRS score had a mean of 39.433±4.67335 and final MADRS score had a mean of 27.1333 ±4.95311. Conclusion: The study clearly conveyed that the patients who had their age below 30 years and who had their 1st pregnancy below 20 years with low educational status and low socio-economic status had a greater chance of postpartum depression. The incidence of PPD was higher in upper middle socio-economic class. The patients who had education status of SSLC had higher incidence of PPD. The postpartum sleep disturbance was evident in all 30 patients studied for the duration of 6 months. Statistical comparison proved that SSRI is more efficient in the management of PPD compared to the TCAs.
Keywords: Clinical Profiling; PPD; SSRIs; TCAs